2022
DOI: 10.1101/2022.07.19.500602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

C. elegans toxicant responses vary among genetically diverse individuals

Abstract: Comprehensive chemical hazard risk evaluations require reproducible, efficient, and informative experimental workflows in tractable model systems that allow for high replication within exposure cohorts. Additionally, the genetic variability of toxicant responses among individuals in humans and mammalian models requires practically untenable sample sizes. Caenorhabditis elegans is a premier toxicology model that has revolutionized our understanding of cellular responses to environmental pollutants and boasts ro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The variation in strain-specific slope comparisons further supports how the incorporation of genetic diversity is necessary to identify anthelmintic responses within a species. Here, we reinforce what previous studies have shown, that C. elegans is a powerful model for assessing the impact of genetic differences on phenotypic variation [23].…”
Section: Anthelmintic Drugssupporting
confidence: 91%
See 1 more Smart Citation
“…The variation in strain-specific slope comparisons further supports how the incorporation of genetic diversity is necessary to identify anthelmintic responses within a species. Here, we reinforce what previous studies have shown, that C. elegans is a powerful model for assessing the impact of genetic differences on phenotypic variation [23].…”
Section: Anthelmintic Drugssupporting
confidence: 91%
“…The custom CellProfiler pipeline generates animal measurements by using four worm models: three worm models tailored to capture animals at the L4 larval stage, in the L2 and L3 larval stages, and the L1 larval stage, respectively, as well as a “multi-drug high dose” (MDHD) model, to capture animals with more abnormal body sizes caused by extreme anthelmintic responses. Worm model estimates and custom CellProfiler pipelines were written using the WormToolbox in the GUI-based instance of CellProfiler [23]. Next, a custom R package, easyXpress (Version 1.0), was then used to process animal measurements output from CellProfiler [17].…”
Section: Methodsmentioning
confidence: 99%
“…A previously described high-throughput fitness assay was used for all measurements of benzimidazole responses [29][30][31]. The assay included growth measurements of 44 replicate populations comprising approximately 50 animals for each strain in each condition, with the exception of N2 in the albendazole condition (Data Available at: https://github.com/ AndersenLab/2022_BZ_Resistance_ben1_Q134H).Each strain was amplified on NGMA plates for four generations, bleach synchronized, and then approximately 50 embryos in 50 μL of K medium [56] were aliquoted into each well of a 96-well plate. The following morning, arrested L1s were given a mixture of HB101 bacterial lysate [57] at a concentration of 5 mg/mL, kanamycin at a concentration of 50 μM, and either 1% DMSO or 30 μM albendazole in 1% DMSO.…”
Section: Crispr-cas9 Editing Of the Q134h(caa>cat) Allele Into The C ...mentioning
confidence: 99%
“…Nematodes affected by anthelmintics have delayed development. Worm model estimates and custom CellProfiler pipelines were written using the WormToolbox in the GUI-based instance of CellProfiler [ 69 ]. Next, a custom R package, easyXpress (Version 1.0), was then used to process animal measurements output from CellProfiler [ 15 ].…”
Section: Methodsmentioning
confidence: 99%